2020
DOI: 10.3389/frobt.2020.561015
|View full text |Cite
|
Sign up to set email alerts
|

Kinesthetic Device vs. Keyboard/Mouse: A Comparison in Home Care Telemanipulation

Abstract: Ensuring care is one of the biggest humanitarian challenges of the future since an acute shortage in nursing staff is expected. At the same time, this offers the opportunity for new technologies in nursing, as the use of robotic systems. One potential use case is outpatient care, which nowadays involves traveling long distances. Here, the use of telerobotics could provide a major relief for the nursing staff, as it could spare them many of those—partially far—journeys. Since autonomous robotic systems are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Xie et al discussed the use of joysticks as a control interface [11]. Ishiguro et al delved into the application of exoskeletons [12], while Gliesche's work compared keyboard and mouse with kinesthetic devices [13]. Nandikolla et al showed that another approach to control the robots can be via braincomputer interfaces (BCI) as a means to command robots using users' brain signals, allowing them to interact with robots in an innovative way [14].…”
Section: Related Workmentioning
confidence: 99%
“…Xie et al discussed the use of joysticks as a control interface [11]. Ishiguro et al delved into the application of exoskeletons [12], while Gliesche's work compared keyboard and mouse with kinesthetic devices [13]. Nandikolla et al showed that another approach to control the robots can be via braincomputer interfaces (BCI) as a means to command robots using users' brain signals, allowing them to interact with robots in an innovative way [14].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, we conduct a supplementary user study to provide additional insight into the effects of the demonstration method to compare the two most common demonstration approaches: teleoperation and kinesthetic guidance. There are studies comparing both teaching approaches, but they were conducted for a single arm [42], [43]. The study in this article looks into this subject from a bimanual perspective.…”
Section: User Study: Teleoperation Versus Kinesthetic Teachingmentioning
confidence: 99%
“…Furthermore, while many studies have explored the effect of shared autonomy and control system design on task performance, a limited number of works have investigated the nature of the interface exposed to the operator and its effects on task performance. Such a comparison has been explored in Gliesche et al (2020) between a keyboard-mouse setup, XBOX controller and a bilateral setup using a haptic device. For a range of patient care tasks, involving grasping and moving a remote and adjusting a camera view, a haptic device was found to improve the speed at which operators carried out tasks, however no subjective differences in mental load were identified.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, for disassembly in hazardous settings, it is suggested that the quality and realism of the feedback, and interface provided to the operator can greatly impact the level of task performance ( Bolarinwa, 2022 ). Nonetheless, the effect of the user interface on such tasks has not been evaluated, and limited comparative studies exist for telerobotics in non-hazardous settings ( Gliesche et al, 2020 ; Singh et al, 2020 ). Specifically, using telerobotics for the application of EV battery disassembly is not well explored, particularly, where damaged batteries present further critical challenges to the process of disassembly.…”
Section: Introductionmentioning
confidence: 99%